2009
DOI: 10.1002/jgm.1344
|View full text |Cite
|
Sign up to set email alerts
|

AAV gene therapy as a means to increase apolipoprotein (Apo) A‐I and high‐density lipoprotein‐cholesterol levels: correction of murine ApoA‐I deficiency

Abstract: The present study demonstrates that systemic delivery of a scAAV8 vector provides a means for efficient liver expression of hApoA-I, thereby correcting the lipid abnormalities associated with murine ApoA-I deficiency. Importantly, the study demonstrates that AAV-based gene therapy can be used to express therapeutic proteins at a high level for a prolonged period of time and, as such, provides a basis for further development of this strategy to treat hApoA-I deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…HDL supplementation agents are also in clinical use, including infusion of synthetic or plasma-purified ApoAI and ApoAI mimetic peptides [13]. Gene addition has also been used to boost plasma ApoAI and HDL in preclinical studies using adenovirus and adeno-associated virus (AAV) vectors for delivery [14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…HDL supplementation agents are also in clinical use, including infusion of synthetic or plasma-purified ApoAI and ApoAI mimetic peptides [13]. Gene addition has also been used to boost plasma ApoAI and HDL in preclinical studies using adenovirus and adeno-associated virus (AAV) vectors for delivery [14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…APOA1 knockout mice lacking a functional APOA1 protein ( 12 ) were provided on a hyperlipidemic LDL receptor (LDLR) knockout background ( 13 ) by Dr. J. A. Kuivenhoven from the Amsterdam Medical Center (Amsterdam, The Netherlands).…”
Section: Animalsmentioning
confidence: 99%
“…Recently, Vaessen et al performed head-to-head comparisons of recombinant AAV-1, -2, -6 and -8 administered by different routes with the use of five different liver-specific promoters in addition to cytomegalovirus as single-stranded or as sc AAV vectors. They found that intravenous administration of scAAV8 results in the highest levels of human APOA1 expression in female Apoa1 -deficient mice (634 mg/dl), which persisted for the duration of the study (15 weeks) [85]. Cimmino and colleagues have extended upon these findings and have recently demonstrated stable long-term plasma levels of APOA1 in deficient mice after portal vein or muscle injection of AAV8.…”
Section: Disorders Associated Primarily With Altered Levels Of Hdl-cmentioning
confidence: 99%